Pembangunan ekonomi yang berkelanjutan: Konsep dasar, pembangunan sosial berkelanjutan dan pembangunan lingkungan berkelanjutan - Illiyyin, Salwa Lafi; Septian, Annisa Ridha Dwi (Maliki Interdisciplinary Journal, 2024)
The concept of sustainable development means that development must meet current needs without reducing, compromising or destroying the environment. Utilizing existing natural resources and creating a favorable environment for life for the next generation. Sustainable development is the struggle to meet everyone’s basic needs and develop into opportunities to fulfill human desires for a better life. Survival is supported by three pillars: social aspects (known as standard human needs), environmental aspects (known as ecology or earth), and economic aspects (known as money or profit). The main goal of sustainable development is to improve people’s welfare by paying attention to the environment. Economic sustainability, social sustainability and environmental sustainability are pillars of sustainable development that need to be developed proportionally. The results of traditional development show that the benefits of development are not evenly distributed.